Effect Of Organic Selenium Supplementation On The Growth Performance Of Tilapia Oreochromis Niloticus - Shelly Pattipeiluhu .; Christian Ernsz Pattipeilohy; Stefanno M. A. Rijoly; Zulham Tomagola (Cita Konsultindo Research Center, 2023)
Selenium is one of the micronutrients that play an important role in fish growth, even though it is needed in small amounts. This study aims to determine the effect of increasing the dose of selenium in feed on tilapia growth. The dose of organic selenium added in the feed is 2 and 4 mg Se/kg of feed with different protein levels, namely 26% and 28%. This study used a complete randomized design or RAL with four treatments and three tests. The fish used are tilapia (Oreochromis niloticus), totaling 35 heads with a size of 5-7 cm and an average weight of 10 ±0.5 g, consisting of 12 pieces of aquarium each filled with 5 fish. The fish are kept for 60 days with a frequency of feeding three times a day at 08.00, 12.00 and 16.00 WIT on an adsatiation basis. This study showed that fish fed with feed containing 4 mg of organic Se/kg of feed and 26% protein showed the best growth performance.